EVALUATION OF THE UNDERGRADUATE COURSE IN ARCHITECTURE AND URBANISM COURSE AT UFMG FROM ENADES 2011, 2014, 2017 AND 2020 (Interdisciplinary Studies Journal, 2024)
Performance evaluation of students of the undergraduate Course in Architecture and Urbanism of the School of Architecture of the Federal University of Minas Gerais (EAUFMG) based on the instruments and results of ENADE for the years 2011, 2014, 2017 and 2020. Methodologically, the study reviewed the concepts and methodologies of the SINAES, the "Course Reports" made available by the Ministry of Education, the components of "General and Specific Training of ENADE Exams" and the respective "CPC" and "IGC" of the Course over the last decade. The primary objective was to subsidize the proposal for curricular reform of the School of Architecture and as secondary, relevant objectives, the enhancement of the teaching-learning process from the analysis of the themes of the exam questions, the "Socioeconomic Questionnaire" and the "Opinion of the graduating students about the IES" are highlighted. Ratifying INEP, the work guided the pedagogical actions of the Course, since it constitutes a reference for the knowledge of the institutional reality and evidences the integrative character of the evaluation.
Keywords: Evaluation; ENADE; Architecture and Urbanism